An Introductory Bibliography for the Study of 1 Enoch - Drawnel, Henryk (The Biblical Annals, 2019)
The article contains elementary information concerning the manuscripts of 1 Enoch, their editions, and scientific literature that deals with the topic. The presentation begins with the list of larger bibliographic collections concerning the Enochic writings, then the Aramaic witnesses preserved in 11 manuscripts found in Qumran Cave 4 are shortly discussed and pertinent information concerning their edition is given. The rest of the study adduces basic details about the manuscripts that contain the translation of the original Aramaic and the history of their publication. By offering a general perspective on the manuscripts of 1 Enoch, with special attention focused on Aramaic evidence, the article leads the reader through the textually and linguistically complicated history of text transmission of this important Jewish composition.